Chronicle Of Bennett C. Riley - Leo E. Oliva (Symphony in the Flint Hills, 2013)
Timeline of events for Major Bennett C. Riley, the first military escort on the Santa Fe Trail in 1829. The efforts of his leadership and the actions of the troops involved showed a need for military protection on the Sante Fe Trail and helped establish a Fort which would be called Fort RIley.
Keywords: military; escort; army; government; territory; settlers; career; Bennett C. Riley; Fort Riley; Junction City; Kansas; Santa Fe Trail; wagon; train; trail; westward; western; merchant; Native American; Indians; Great Plains; troops; soldiers; caravan; Leavenworth; Mexican; Oregon-California